Case report: Injected corticosteroids for treating leprosy isolated neuritis - Spitz, Clarissa Neves; Pitta, Izabela Jardim Rodrigues; Andrade, Ligia Rocha; Sales, Anna Maria; Sarno, Euzenir Nunes; Villela, Nivaldo Ribeiro; Pinheiro, Roberta Olmo; Jardim, Marcia Rodrigues (Frontiers in Medicine, 2023)
One of the main manifestations of leprosy is the impairment of the peripheral nerves, and diagnosis and treatment are important to reduce the impact of respiratory impairment that can cause deformities and physical disabilities in the course of the disease. Leprosy neuropathy can be acute or chronic and neural involvement can occur before, during or after multidrug therapy, especially during reactional episodes, when neuritis occurs. Neuritis cause loss of function and can be irreversible if left untreated. The recommended treatment is with corticosteroid therapy, usually in an oral regimen at an immunosuppressive dose. However, in patients with clinical conditions that restrict its use or focal neural involvement, they may benefit from the use of ultrasound-guided perineural injectable corticosteroids for an individualized approach and with serial follow-up. In this study, we report two cases that demonstrate how the treatment and follow-up of patients with neuritis secondary to leprosy, using new techniques, can occur in a more individualized way. The use of nerve conduction study in association with neuromuscular ultrasound to monitor the response to treatment with injected steroids at the focus of the neural inflammation provides new perspectives and options for this profile of patients.